2016
DOI: 10.4191/kcers.2016.53.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Oyster Shell Powders for Water Quality Improvement of Lakes by Algal Blooms Removal

Abstract: In this year, Koreans have a shortage in agricultural and drinking water due to severe algal blooms generated in major lakes. Waste oyster shells were obtained from temporary storage near the workplace at which oysters were separated from their shells. Heating (1000 o C for 1 h in air) was employed to convert raw oyster shell powders into calcium oxide powders that reacted efficiently with phosphorus and nitrogen to remove algal blooms from eutrophicated wastewater. As the dispersed amount of heated oyster she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 13 publications
(9 reference statements)
1
14
0
Order By: Relevance
“…The main chemical composition of ROSP is 92.08% of calcium carbonate (CaCO 3 ) [17]. ROSP was calcined at ambient air condition inside an electric furnace at a constant temperature of 900°C for 1 h. After that heat treatment, it is mixed with some calcium carbonate containing CO 2 portion and most of crystalline CaO [18]. The crystalline CaO turned to be a hydrated form of calcite, namely [Ca(OH) 2 ].…”
Section: Preparation Of Tospmentioning
confidence: 99%
“…The main chemical composition of ROSP is 92.08% of calcium carbonate (CaCO 3 ) [17]. ROSP was calcined at ambient air condition inside an electric furnace at a constant temperature of 900°C for 1 h. After that heat treatment, it is mixed with some calcium carbonate containing CO 2 portion and most of crystalline CaO [18]. The crystalline CaO turned to be a hydrated form of calcite, namely [Ca(OH) 2 ].…”
Section: Preparation Of Tospmentioning
confidence: 99%
“…The lanthanum modified bentonite (Phoslock™) and the and Modified Zeolite (Z2G1) represents the most innovative remediation materials (Copetti et al 2016;Zamparas and Zacharias 2014). A study realized by Huh et al (2016) showed that heated oyster shell powders is also a potential material to reduce the presence of phosphate and nitrogen in eutrophicated waters.…”
Section: Restorationmentioning
confidence: 99%
“…Visible transparency of algal freshwater was also gradually converted from dark green to colorless according to the alteration of added amounts of calcined powders as shown in Fig. 5 [89]. For the total pollutant load of the algal solution, the mean removal (or reduction) efficiency of total phosphorus (T-P), total nitrogen (T-N), and chemical oxygen demand (COD) was recorded at 96.5%, 91.4%, and 33.8%, respectively [89].…”
Section: Limementioning
confidence: 99%
“…5 [89]. For the total pollutant load of the algal solution, the mean removal (or reduction) efficiency of total phosphorus (T-P), total nitrogen (T-N), and chemical oxygen demand (COD) was recorded at 96.5%, 91.4%, and 33.8%, respectively [89]. The calcium hydroxide and carbonation combination in algae-containing water significantly contributed to improve water quality which is very dependent on the addition amount of calcined oyster shell powder [90].…”
Section: Limementioning
confidence: 99%
See 1 more Smart Citation